Cortical Venous Changes on Susceptibility-Weighted Imaging Predict the Cerebral Collateral Circulation as Confirmed by Digital Subtraction Angiography - Zhan, Yun-Hao; Chen, Yang-Kun; Li, Run-Xiong; Luo, Gen-Pei; Wu, Zhi-Qiang; Liu, Yong-Lin; Xiao, Wei-Min; Hu, Wei-Dong; Xie, Cai-Qin (Frontiers in Neurology, 2021)
Objective: Asymmetric cortical vein sign (ACVS) shown on susceptibility-weighted imaging (SWI) can reflect regional hypoperfusion. We investigated if ACVS could predict the cerebral collateral circulation (CC) as assessed by digital subtraction angiography (DSA) in acute ischemic stroke patients with ipsilateral severe stenosis/occlusion of the anterior circulation. Methods: Clinical data and imaging data of 62 acute ischemic stroke patients with ipsilateral severe stenosis or occlusion of the anterior circulation confirmed by DSA were collected retrospectively. Participants underwent magnetic resonance imaging, including a SWI sequence. ACVS was defined as more and/or larger venous signals in the cerebral cortex of one side of SWI than that in the contralateral side. ACVS was measured using the Alberta Stroke Program Early Computed Tomography score based on SWI. The grading of the cerebral CC was judged using DSA. Results: Of the 62 patients, 30 patients (48.4%) had moderate-to-severe ACVS. According to DSA assessment, 19 patients (30.6%) had a good CC (grade 3–4) and 43 (69.4%) patients had a poor-to-moderate CC (grade 0–2). Among the 30 patients with moderate-to-severe ACVS, only 3 (10%) patients had a good CC, and 27 (90%) patients had a poor-to-moderate CC; and among the 32 patients with none or mild ACVS, 16 (50%) of them had a good CC and the other 50% had a moderate-to-severe CC. We constructed two logistic regression models, with ACVS grading and None or mild ACVS entered into the models respectively, together with age and large-artery occlusion. In model 1, no ACVS (compared with severe ACVS; OR = 40.329, 95%CI = 2.817–577.422, P = 0.006), mild ACVS (compared with severe ACVS; OR=17.186, 1.735–170.224, 0.015) and large-artery occlusion (OR=45.645, 4.603–452.592, 0.001) correlated with a good CC. In model 2, none or mild ACVS (OR = 36.848, 95%CI = 5.516–246.171, P < 0.001) was significantly associated with a good CC as judged by DSA, adjusted by age and large-artery occlusion . Conclusions: Cortical venous changes in SWI may be a useful indicator for the cerebral CC as confirmed by DSA.